2006
DOI: 10.1007/s00464-005-0829-7
|View full text |Cite
|
Sign up to set email alerts
|

The importance of classification in sympathetic surgery and a proposed mechanism for compensatory hyperhidrosis: experience with 464 cases

Abstract: Different procedures are recommended for different sympathetic disorders according to the classification. The higher the level of sympathetic ganglion blockade, the higher is the regret rate. Therefore, for T2 and T3 ganglion, endoscopic thoracic sympathetic block by the clipping method is strongly recommended because of its reversibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
89
1
10

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(101 citation statements)
references
References 16 publications
1
89
1
10
Order By: Relevance
“…Some have argued that clipping cannot be considered to be a reversible technique (15,16), while others have suggested that clips should be removed between the first ten days and the first month after sympathetic clipping to ensure recovery of the sympathetic nerves (6,17). We assume that clipping removal was not done in time for reversal; therefore, we also believe clipping removal is not a reversible technique.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some have argued that clipping cannot be considered to be a reversible technique (15,16), while others have suggested that clips should be removed between the first ten days and the first month after sympathetic clipping to ensure recovery of the sympathetic nerves (6,17). We assume that clipping removal was not done in time for reversal; therefore, we also believe clipping removal is not a reversible technique.…”
Section: Discussionmentioning
confidence: 99%
“…For palmar hyperhidrosis, there is a slightly higher risk of CS with an R3 interruption but a risk of moister hands with an R4 interruption. Patients feel more comfortable when a certain minimal moistness is maintained and complete exsiccation is avoidable (8,17,21).…”
Section: Discussionmentioning
confidence: 99%
“…The surgeon needs adequate and continuous relaxation to prevent injuries during the surgery. The most common side effect of this method is compensatory sweating due to thermoregulatory mechanisms [5]. Pneumothorax, haemothorax, chylothorax, pleural effusion, lung injury, Horner's Syndrome, nasal obstruction, rhinitis, wound infection, and intercostal neuralgia may be seen intra-and peri-operatively.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism whereby CS occurs is unclear, but it is thought to occur due to an abnormal thermoregulatory response after sympathectomy, whereby residual sweat glands increase their activity in an attempt to compensate for the loss of neural regulated sweat glands. It is also possible that CS occurs due to an altered feedback mechanism in the hypothalamus [53]. The intensity of CS is subjective and can vary among patients from mild to disabling.…”
Section: Complications and Side Effects Of Endoscopic Thoracic Sympathementioning
confidence: 99%